2021
DOI: 10.1093/brain/awab167
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response in amyotrophic later sclerosis: results of a phase 2 trial

Abstract: Strong evidence suggests that endoplasmic reticulum (ER) stress plays a critical role in the pathogenesis of amyotrophic lateral sclerosis (ALS) through an altered regulation of proteostasis. Robust preclinical findings demonstrated that guanabenz selectively inhibits ER stress-induced eIF2α-phosphatase allowing misfolded protein clearance, reduces neuronal death and prolongs survival in in vitro and in vivo models. Its efficacy and safety in ALS patients are unknown. To address these issues, we conducted a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 72 publications
(63 reference statements)
0
35
0
Order By: Relevance
“…The striking beneficial effects of GBZ in VWM mice have led to the first clinical trial in VWM (https://www.trialregister.nl/trial/7260 and https://www.clinicaltrialsregister.eu/ctr-search/trial/2017-001438-25/NL). Translating GBZ treatment into clinical studies comes with concerns regarding α2‐adrenergic side effects, 59 although rapid habituation is also seen in clinic 60 and dose levels with similar exposure as used in the current study have proven safe in adults. Our study makes clear that S1 is not simply a GBZ replacement without α2‐adrenergic effects for the treatment of VWM.…”
Section: Discussionmentioning
confidence: 90%
“…The striking beneficial effects of GBZ in VWM mice have led to the first clinical trial in VWM (https://www.trialregister.nl/trial/7260 and https://www.clinicaltrialsregister.eu/ctr-search/trial/2017-001438-25/NL). Translating GBZ treatment into clinical studies comes with concerns regarding α2‐adrenergic side effects, 59 although rapid habituation is also seen in clinic 60 and dose levels with similar exposure as used in the current study have proven safe in adults. Our study makes clear that S1 is not simply a GBZ replacement without α2‐adrenergic effects for the treatment of VWM.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent clinical trial in which sporadic patients were treated with guanabenz to evaluate safety and efficacy, there was a surprising result that showed that patients with bulbar onset did not progress to a higher stage during the course of the study [ 151 ]. However, some patients drop the treatment due to secondary effects of Guanabenz [ 151 ]. Nevertheless, some of these drugs have secondary effects in other tissues.…”
Section: The Logic For Therapeutic Isr Modulation In Different Fals M...mentioning
confidence: 99%
“…GSK2606414 showed some weight loss and mild hyperglycemia in a mouse prion model [ 152 , 153 ] whereas, in ALS patients, guanabenz showed adverse effects such as hypotension, fatigue, and drowsiness that could be related with its alpha-2 adrenergic receptor activity. However, no serious adverse events were observed with respect to the placebo group [ 151 ]. For those reasons, clinical trials have evaluated the safety, availability, and tolerability of ISR modulation with sephin1 (IFB-088, that lacks the alpha-2 adrenergic receptor activity and blood pressure lowering adverse effects have not been observed [ 154 ]) instead of with guanabenz.…”
Section: The Logic For Therapeutic Isr Modulation In Different Fals M...mentioning
confidence: 99%
“…The next, no less important point is the phenomenon of endoplasmic reticulum (ER) stress, which is caused by the accumulation of unfolded, defective proteins in the ER lumen [43]. This pathophysiological process is typical of most neurodegenerative diseases and may be a therapeutic target [44][45][46][47][48][49]. For the formation of the tertiary structure of a protein, disulfide bonds are important, the formation of which is mediated by the enzyme protein disulfide isomerase, which, in turn, is activated by oxidation.…”
Section: Genetically Coded Sensors Of Pathological Cell Processesmentioning
confidence: 99%